PKM Pembuatan Mochi Rainbow Fla (MORFLA) - Ratnah S; Nur Arisah; Nurjannah Nurjannah; Mustari Mustari; Sitti Hajerah Hasyim (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
In Indonesia, the use of glutinous rice flour is still limited to foods containing carbohydrates and tends to be used to produce foods that are filling. One of the foods made from glutinous rice flour is mochi. Mochi is one of the foods that is still rarely found in society because mochi is one of the modern foods whose method of making is still unknown to many people. Therefore, innovations to mochi cakes are needed to attract the interest of many people to buy and have an interest in making mochi for consumption or for sale in order to generate economic value that can be marketed both domestically and internationally. The methods used in this activity include lectures, questions and answers or discussions, and training and mentoring carried out in Manggala District, Makassar City for 2 weeks. The results obtained are: (1) Training on making Rainbow Fla Mochi was responded well by participants; (2) High interest and motivation from training participants greatly supports the transfer of knowledge and skills from the servants to the training participants, so that the training material provided can be absorbed by all; and (3) The product of the Rainbow Fla Mochi making training can be consumed daily and can be used as a community entrepreneurial product.